In-order transition-based parsing for Vietnamese - Bauer, John; Bui, Hung; Thai, Vy; Manning, Christopher (Journal of Computer Science and Cybernetics, 2023)
In this paper, we implement a general neural constituency parser based on an in-order parser. We apply this parser to the VLSP 2022 Vietnamese treebank, obtaining a test score of .8393 F1, top of the private test leaderboard. Earlier versions of the parser for languages other than Vietnamese have already been included in the publicly released Python package Stanza [35 ]. The next Stanza release will include the Vietnamese model, along with all of the code used in this project.